2007
DOI: 10.1677/joe-07-0272
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-stimulated growth of the rat prostate may be driven by tissue hypoxia and hypoxia-inducible factor-1α

Abstract: Testosterone-stimulated growth of the ventral prostate (VP) in castrated rats is preceded by angiogenesis, but the mechanisms coordinating vascular and tissue growth are unknown. Adult rats were castrated and some treated with testosterone. Tissue hypoxia was studied morphologically using the hypoxia marker pimonidazole (Hypoxyprobe), hypoxia-inducible factor-1 (HIF-1) a, vascular endothelial growth factor (VEGF), and carbonicanhydrase 9 (CA-9) levels by western blotting and quantitative RT-PCR. In the intact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
4
17
0
Order By: Relevance
“…However, the observation that ischemic lims from ARKO mice exhibited marked edema and a dusky red-colored skin appearance on day 1 after surgery are consistent with exaggerated ischemia in the operated limbs of ARKO mice. Since previous studies showed that castration rapidly reduces blood flow to the rat ventral prostate gland with acceleration of epithelial cellular apoptosis and tissue hypoxia 53, 54 and since we have reported that AR deficiency reduces nitric oxide bioavailability 22 , lack of androgen action may lead to prominent tissue hypoxia due to circulatory insufficiency. Although further investigations are needed to clarify this issue, we speculate that the enhanced Hif1a and Vegfa expression levels reflect a more severe acute ischemic condition in ARKO mice than in WT mice.…”
Section: Discussionmentioning
confidence: 82%
“…However, the observation that ischemic lims from ARKO mice exhibited marked edema and a dusky red-colored skin appearance on day 1 after surgery are consistent with exaggerated ischemia in the operated limbs of ARKO mice. Since previous studies showed that castration rapidly reduces blood flow to the rat ventral prostate gland with acceleration of epithelial cellular apoptosis and tissue hypoxia 53, 54 and since we have reported that AR deficiency reduces nitric oxide bioavailability 22 , lack of androgen action may lead to prominent tissue hypoxia due to circulatory insufficiency. Although further investigations are needed to clarify this issue, we speculate that the enhanced Hif1a and Vegfa expression levels reflect a more severe acute ischemic condition in ARKO mice than in WT mice.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, if any of these co-factors is limited, HIF-1α becomes stabilized and activated regardless of oxygen level. In addition, to this hydroxylation process, HIF-1α is known to be induced by some growth factors which accelerate the de novo synthesis of HIF-1α protein [9,10], and, similarly, testosterone has also been recently reported to stimulate HIF-1α synthesis even under normoxic conditions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…33 Furthermore, transient epithelial cell hypoxia has been shown to rapidly increase HIF-1a and its downstream targets such as VEGF in rat prostate tumors. 34 Our investigation tested the hypothesis that MSeA inhibits HIF1a and its downstream targets involved in growth of invasive prostate cancer under hypoxic conditions.…”
mentioning
confidence: 98%